Assessment of housing provision in third world cities: the case study of Bulawayo city council - Ngwenya, Nobuhle (Midlands State University, 2017)
The research sought to assess the housing provision in third world cities using the case study of Bulawayo City Council. The study assessed the housing challenges in line with the requirements of the sustainable development Goal (SDG) Goal 11 which calls for cities to be inclusive, safe, resilient and sustainable. The imbalance between housing demand and housing supply in urban Bulawayo was identified as the statement of the problem. The purpose of the study was to investigate the factors hindering BCC in the provision of adequate housing, to identify socio-economic problems associated with inadequate housing in Bulawayo, to identify measures taken by BCC in addressing housing shortages in Bulawayo and to come up with recommendations on ways to improve the housing challenges in Bulawayo. The literature reviewed revealed that the housing challenge was a global issue and not limited to third world cities. The housing challenges were fuelled by overpopulation in cities, shortage of residential space in cities and the in- affordability of housing. The literature review also brought out the economic and social problems associated with the housing challenges. Singapore and South Africa were used as points of reference as they share the same housing problems as those experienced by Zimbabwe. The social theory by Thomas Hobbes was employed in the theoretical framework; the theory asserts that the citizens entrusts the local authority to provide them with efficient services and the government has a moral obligation to provide the services and is guided by the natural law. The researcher used both the qualitative and quantitative data design. The study used questionnaires, observations and interviews for data gathering. The research findings were presented graphically, statistically and descriptively. The findings confirmed that the housing challenges had led to the development of squatter camps around the city. The life in the squatter camps fuelled socio- economic problems to the inhabitants. The use of the open bush system, the failure to acquire quality education, the lack of access to primary health care and the discrimination faced by the inhabitants had negative connotations both economically and socially. BCC has failed to keep up with the growing population and this had resulted in the ballooning of the housing waiting list to 110 000. The economic depression which had force matched key employees out of the country left BCC with no capacity to service its stands in- house; and the shortage of land were discovered as hindrances in the housing provision. Finally the researcher recommended that to ease housing challenges BCC had to; avail low cost housing to house the urban poor who have been driven to squatter camps, use its land sparingly by encouraging the construction of vertical buildings instead of the horizontal buildings when constructing residential houses, erect satellite clinics for easy access to primary health care and construct public toilets in squatter camps.